Perceived oral health beliefs, traditional practices, and oral health status of nomads of Tamilnadu: A cross-sectional study - R Sindhu; Sunayana Manipal; Raj Mohan; V V Bharathwaj; N Divya Lalitha; D Prabu (Journal of Family Medicine and Primary Care, 2020)
Aim: To assess the perceived oral health beliefs, traditional practices, and oral health status of nomads. Methods: A cross-sectional study was conducted among 115 nomads residing in various places of Tamilnadu. Information regarding socio-demographics such as age, gender, occupation, and place of residence were obtained. Study participants were interviewed with a pre-tested questionnaire consisting questions related to oral health beliefs and oral health practices. Clinical examination was carried out to record the oral health status using a proforma. Results: A significant Chi-square association was found with oral health-related beliefs (P < 0.01). However, 30.9% had perceived strong beliefs, 64.3% of the subjects used toothbrush, and 20% had at least one oral mucosal lesion. Conclusion: A significant proportion of nomads had perceived oral health beliefs, which had a significant association with their traditional practices and their oral health was much deteriorated.